UJI AKTIVITAS ANTIBAKTERI INFUSA BIJI PINANG (Areca catechu Lin.) TERHADAP Streptococcus mutans - ., Dey Shie (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Dental caries is a disease that attacks and damagetooth enamel. Streptococcus mutans is a pathogenic bacteria in themouth which is primary causative agent of dental caries. Theempirical data shows that boiled water of areca seed leaves is usedby local people as herbal medicine. Previous research shows ofethanol extract from areca seed has antibacterial property.Objective: The objective of this research was to know antibacterialproperty of areca seed leaves infusion againts Streptococcusmutans by determining minimum inhibitory concentration (MIC).Methods: Phytochemical screening of areca seed leaves infusionwas performed by test tube method. Test of antibacterial activitywas done by using dilution method againts Streptococcus mutans.Data was analized with One Way Anova Test, then continued with Post-Hoc LSD Test and Pearson Correlation Test. Result:Secondary metabolite contents of kesum leaves infusion areflavonoid, tannin, and saponin. Statistical analysis show that arecaseed leaves infusion concentrations that can reduce colony countwith a significant number are 30% infusion concentration.Spearman correlation test show that bacterial colony growthvariabel has a very strong inverse correlation (r= -0,976) withinfusion concentration. Conclusion: Areca seed leaves infusionhas antibacterial activity againts Streptococcus mutans.Keyword: Antibacterial, Infusion, Areca seed, Streptococcusmutans 1) Medical School, Faculty of Medicine, University of TanjungpuraPontianak, West Kalimantan 2) Pharmacy School, Faculty of Medicine, University ofTanjungpura Pontianak, West Kalimantan 3) Medical School, Faculty of Medicine, University of TanjungpuraPontianak, West Kalimantan